The value of education for novice academic staff from the perspective of selected aspects of self-concept - Koribska, Iva (e-Pedagogium, 2019)
This article explores the value of education for novice academic staff from the perspective of selected aspects of self-concept. The main objective was to find out what priority education has in the value orientation of respondents. Furthermore, the factors that influence the value of education of respondents' cognitive, emotional and conative aspects of self-concept were analysed. A semi-structured interview was chosen as a research tool and the respondents' responses have undergone open, axial and selective coding.
Keywords: Keywords: novice academic staff; doctoral study; value; value orientation; self-concept; self-efficacy awareness (self-efficacy); self-esteem; self-realization.